Characterization of an allelic series in the MONOPTEROS gene of arabidopsis. Issue 2 (5th December 2013) - Odat, Osama; Gardiner, Jason; Sawchuk, Megan G.; Verna, Carla; Donner, Tyler J.; Scarpella, Enrico
Summary Patterning of numerous features of plants depends on transduction of the auxin signal. Auxin signaling is mediated by several pathways, the best understood of which relies on the function of the MONOPTEROS (MP) gene. Seven mp mutant alleles have been described in the widely used Columbia background of Arabidopsis: two extensively characterized and five only partially characterized. One of these five mp alleles appears to be extinct and thus unavailable for analysis. We show that two of the four remaining, partially characterized mp alleles reported to be in the Columbia background are in fact not in this background. We extend characterization of the remaining two Columbia alleles of mp, and we identify and characterize four new alleles of mp in the Columbia background, among which the first low‐expression allele of mp and the strongest Columbia allele of mp. These genetic resources provide the research community with new experimental opportunities for insight into the function of MP‐dependent auxin signaling in plant development. genesis 00:1–9. © 2013 Wiley Periodicals, Inc.